The Cultural Images of Community Life among the Catholic Sundanese and Javanese - Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
This article is a result of an ecclesiological and catechetical survey conducted among the Catholics of two parishes in Java. Two themes were explored, namely, (1) relationship of the self and the community, and (2) sharing of experiences as an encounter of faith. These were put within the larger project to search for images from within the local cultures that may support catechetical materials about the church. This survey was intended to open the theological discourse of the church to the local cultures without proposing particular models to the believers. It explores the sociocultural realities of the local believers without direct reference to the church. It refers to faith and religious experiences of the believers but only insofar as they are related to the people’s understanding of the self and the community. There were traces of how the believers relate themselves as cultural persons to the society as a community. Another presumption behind the themes was that sharing of faith experiences might happen through the daily conversations in the community life. These themes can corroborate the exploration of the community life among the believers in Java, since it is through the sharing of faith experiences that the people may see their community life differently. By considering faith in its broadest sense, this article wants to trace the possible cultural images that may shape the believers’ cultural preferences in living their life as church members. An emphasis will be put on the daily matters of the believers’ responses in order to collect the cultural images ‘from below’. Keywords :*Culture, *Images, *Religious community, *Sundanese, *Javanese, *church, *the believer's experience, *relationships, *local culture, *ecclesiology, *faith encounter, *cultural preference, *community life